Psychometric characteristics of a pisa-based scientific literacy assessment instrument for ecology: a rasch model analysis - Erik Nanda Putra Putra; Lufri Lufri; Syafri Anwar; Yuni Ahda (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
Scientific literacy is an essential competency for the 21st century, yet Indonesian students continue to demonstrate relatively low levels of achievement. This study aimed to analyze the psychometric characteristics of a PISA-based scientific literacy assessment instrument on ecology during the field-testing phase using the Rasch model. The study involved 40 students who completed a 45-item assessment. Data were analyzed using Winsteps based on three Rasch indicators: person–item targeting, item fit, and separation index. The results showed appropriate targeting, with a 0.45-logit difference between the mean student ability and mean item difficulty. A total of 43 of the 45 items (95.6%) met the Rasch model fit criteria. The person separation index of 1.71 and item separation index of 2.18 classified students' abilities and item difficulties into three distinct strata. Overall, the findings indicate that the instrument demonstrates adequate psychometric characteristics for measuring scientific literacy in ecology. However, the relatively modest person separation suggests that additional items targeting lower ability levels may further improve the instrument's measurement precision.